Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Can you please check if i solved this limit correctly?

$\lim_{x \to 1} \frac{\sin{(1-x)}}{\sqrt{x}-1} $

To skip writing of code , I'll just explain what i did .. First, I multiplied the expression by $\frac{\sqrt{x}+1}{\sqrt{x}+1}$. Then i got $\frac{\sin{(1-x)} * (\sqrt{x}+1)}{x-1}$. Next i pulled out the minus in from of the brackets in denumerator so i got: $\frac{\sin{(1-x)} * (\sqrt{x}+1)}{-(1-x)}$. Since $\frac{\sin{(1-x)}}{1-x}$ is equal to 1, I am left with $ -(\sqrt{x}+1)$. After exchanging x with 1 i get -2 as a result. Did i do this correctly?

share|cite|improve this question
I think it is correct. – user46090 Oct 28 '12 at 10:21
It is correct for sure – Host-website-on-iPage Oct 28 '12 at 10:23
One note: $\frac{\sin{(1-x)}}{1-x} \ne{1}$ but $\lim\limits_{n\rightarrow\infty}\frac{\sin{(1-x)}}{1-x}=1$. – M. Strochyk Oct 28 '12 at 10:38
Yea, sorry, I'm new to limits so i forget to write it xD. Thanks – Transcendental Oct 28 '12 at 11:44
up vote 0 down vote accepted

Applying L'Hospital (L'H), we get:

$$\lim_{x\to 1}\frac{\sin(1-x)}{\sqrt x-1}\stackrel{L'H}=\lim_{x\to 1}\frac{-\cos(1-x)}{\frac{1}{2\sqrt x}}=\frac{-1}{\frac{1}{2}}=-2$$

The above makes it sure you got the correct result in your development and that this last was very probably correct.

share|cite|improve this answer
I would have applied the rule but i didn't do derivatives yet and Wikipedia says that it has something to do with derivatives :D – Transcendental Oct 28 '12 at 11:47

$$\lim_{x \to 1} \frac{\sin{(1-x)}}{\sqrt{x}-1}$$

$$=\lim_{x \to 1} \frac{\sin (1-x)(\sqrt x+1)}{x-1}$$

Putting $h=1-x,$ so $h\to 0$ as $x\to 1,$ $$=-\lim_{h \to 0} \frac{\sin h(\sqrt {1-h}+1)}h$$

$$=-\lim_{h \to 0} \frac{\sin h}h \cdot \lim_{h \to 0}(\sqrt {1-h}+1)$$

$=-1\cdot 2=-2$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.